2013
DOI: 10.1021/la3051115
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Protein Adsorbing Coatings from Clickable PEG Nanogel Solutions: Benefits of Attachment under Salt-Induced Phase Separation Conditions and Comparison with PEG/Albumin Nanogel Coatings

Abstract: Clickable nanogel solutions were synthesized by using the copper catalyzed azide/alkyne cycloaddition (CuAAC) to partially polymerize solutions of azide and alkyne functionalized poly(ethylene glycol) (PEG) monomers. Coatings were fabricated using a second click reaction: a UV thiol-yne attachment of the nanogel solutions to mercaptosilanated glass. Because the CuAAC reaction was effectively halted by the addition of a copper-chelator, we were able to prevent bulk gelation and limit the coating thickness to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Elbert and co‐workers exploited the concept of separate, sequential “click” reactions for the preparation and attachment of PEG nanogels to glass surfaces in order to prepare protein resistant coatings . The PEG nanogels were prepared via CuAAC of multiarmed PEG‐azide and PEG‐alkyne monomers.…”
Section: Click Chemistry For Functionalization Of Reactive Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbert and co‐workers exploited the concept of separate, sequential “click” reactions for the preparation and attachment of PEG nanogels to glass surfaces in order to prepare protein resistant coatings . The PEG nanogels were prepared via CuAAC of multiarmed PEG‐azide and PEG‐alkyne monomers.…”
Section: Click Chemistry For Functionalization Of Reactive Particlesmentioning
confidence: 99%
“…Then, radical thiol–yne reaction was used to attach the nanogels to mercaptosilanated glass. Additional surface crosslinking of the nanogel coating was performed via CuAAC of residual end groups after attachment to the glass substrate …”
Section: Click Chemistry For Functionalization Of Reactive Particlesmentioning
confidence: 99%
“…Nanogels, formed by physically or chemically cross‐linked polymer networks with nanoscale size, have been widely researched in the fields of tissue engineering, photonic materials, drug delivery, dental materials, modifiers for coatings and polymer composites, because of their versatile structures, large number of chain ends and the ability to incorporate stimuli‐responsive functionalities …”
Section: Introductionmentioning
confidence: 99%
“…Nanogels, which are internally crosslinked and cyclized single or multi-chain polymeric particles with three-dimensional polymer networks 13 , have great potential for use in drug delivery 14 , dental materials 15 , tissue engineering 16 , photonic materials 17 , modifiers for coatings and polymer composites 18 because of their tunable chemical composition and three-dimensional physical structures, large number of chain ends, good mechanical properties, and biocompatibility. It has been demonstrated that high molecular weight, reactive nanogels of approximately 10 nm in dimension when dispersed in and swollen by matrix monomer can be used to reduce polymerization shrinkage and stress without compromise to other critical polymer properties 19 and help reinforce the mechanical properties of the final polymer network by physical entanglement and potential covalent crosslinking between nanogel and the resin matrix.…”
Section: Introductionmentioning
confidence: 99%